The Influences of Reputation, Financial Statement Transparency, Accountability, Religiosity, and Trust on Interest in Paying Zakat of Profession - Jayanto, Prabowo Yudo; Munawaroh, Siti (Jurnal Dinamika Akuntansi, 2019)
This research aims at examining the influence of reputation, financial statement transparency, accountability, religiosity, and trust on interest in paying zakat of profession. The population of this study was muzaki who paid zakat at BAZNAS and LAZ Pati Regency. The sampling technique used in this study was purposive sampling technique, which was obtained by 73 respondents. The data analysis technique used in this research was Structural Equation Modelling (SEM) based on Partial Least Square (PLS) with SmartPLS 3.0 analysis tool. Originality in this study is zakat management organization chosen to be the object of the research, BAZNAS and LAZ at Pati Regency. This is because the phenomenon that occurs is still lack of optimism of zakat accumulation due to the lack of muzaki interest in paying zakat. Therefore, many muzaki distribute their zakat of profession directly to mustahik and it causes injustice among mustahik. The result of the research reveals that reputation, financial statement transparency, religiosity and trust have positive and significant effect on interest in paying zakat of profession. Accountability shows that there is no significant influence on interest in paying zakat of profession. According to the result, it can be concluded that the better the reputation, financial statement transparency and accountability of zakat management organization, the higher the interest in paying zakat of profession through zakat management organization. Furthermore, the higher the religiosity and trust of muzaki towards zakat management organization, the higher the interest in paying zakat of profession through zakat management organization.